A Novel Case of Symptomatic BK Viraemia in a Patient Undergoing Treatment for Hodgkin Lymphoma. (24th June 2014) - Perram, Jacinta; Estell, Jane
Abstract : Symptomatic BK viral infection in the immunocompromised host is well described, most commonly seen in renal transplant recipients, bone marrow transplant recipients, and HIV positive patients. The present case describes a novel clinical scenario of symptomatic urological BK virus infection in a patient receiving treatment for Hodgkin lymphoma. This case highlights the importance of casting a wide diagnostic net for adverse events encountered with novel therapeutic agents or regimens.